Nickel brazing material with excellent wettability
A nickel brazing filler metal with controlled compositions addresses the challenge of low melting and high corrosion resistance, enabling efficient brazing with reduced energy costs and improved wettability for stainless steel heat exchangers.
Patent Information
- Application Number
- JP2021089923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-28
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-05-28
AI Technical Summary
Existing nickel brazing filler metals for stainless steel heat exchangers face challenges in achieving both low melting temperatures and good corrosion resistance, with many failing to provide sufficient wettability and spreadability when brazing temperatures are reduced.
A nickel brazing filler metal composition with specific ranges of Cr, P, B, Cu, Mo, and Si, along with optional Co, Fe, and Mn, ensuring a melting temperature of 1000°C or less, a wax spreading coefficient of 10 or more, and corrosion resistance below 0.50 mg/m²·s, enhancing wettability and corrosion resistance.
The new filler metal achieves reduced brazing temperatures with excellent wettability and corrosion resistance, suitable for stainless steel heat exchangers, reducing energy costs and maintaining performance in acidic environments.
Smart Images

Figure 0007659441000004 
Figure 0007659441000001 
Figure 0007659441000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a brazing filler metal used in heat exchanger applications such as general-purpose heat exchangers, water heaters, and waste heat recovery devices, and suitable for joining various stainless steel members. The present invention relates to a nickel brazing filler metal that has good corrosion resistance, and in particular has a lower melting temperature than general-purpose nickel brazing filler metals, and is excellent in wettability and spreadability. [Background technology]
[0002] Conventionally, nickel brazing filler metals have been used in stainless steel heat exchangers used for refrigerant evaporators, condensers, hot water supply, etc., in environments where oxidation resistance and corrosion resistance are required. General-purpose nickel brazing filler metals for joining various stainless steel members include BNi2 and BNi5 specified in JIS Z 3265:1998 "Nickel brazing filler metals," as well as Ni-Cr-P-Si brazing filler metals described in, for example, Patent Document 1 below.
[0003] In recent years, there has been a strong demand for reducing energy costs during brazing work, and efforts to lower the brazing temperature have been made. For this reason, nickel brazing filler metals with lower melting temperatures than general-purpose products are in demand. In view of this situation, BNi2, BNi5, and the Ni-Cr-P-Si brazing filler metals described in Patent Document 1 all have melting temperatures exceeding 1000°C, and therefore sufficient wettability cannot be obtained when the brazing temperature is lowered.
[0004] In order to solve such problems, the use of BNi6 and BNi7, which have low melting temperatures, as specified in JIS Z 3265:1998 "Nickel Brazing Filler Metal", and BNi12, as specified in AWS A 5.8 / A5.8M:2004, is being considered. In addition, new brazing filler metals with low melting temperatures have been proposed in recent years, for example, as described in the following Patent Documents 2 to 7.
[0005] However, both BNi6 and BNi7 have a problem of insufficient corrosion resistance. BNi12 has excellent corrosion resistance and a liquidus temperature below 1000°C, but has a problem of poor wettability compared to BNi6 and BNi7. Although the examples of Patent Documents 2 to 7 listed below describe brazing filler metals with lower melting temperatures than general-purpose nickel brazing filler metals, there are cases where the liquidus temperature exceeds 1000°C, cases where the wettability is not fully satisfactory even if the melting temperature is low, and problems such as insufficient corrosion resistance.
[0006] As described above, the general-purpose brazing filler metals that have been used up to now and the nickel brazing filler metals described in Patent Documents 1 to 7 have the above-mentioned problems, and at present, no nickel brazing filler metal has been proposed that has both good corrosion resistance and the property of being able to achieve a reduction in the brazing temperature (sufficiently large wet spreadability). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 3168158 [Patent Document 2] JP 2007-75867 A [Patent Document 3] JP 2009-202198 A [Patent Document 4] JP 2011-110575 A [Patent Document 5] JP 2012-55914 A [Patent Document 6] WO2015 / 156066 publication [Patent Document 7] JP 2017-131968 A Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, there has been a strong demand for reducing energy costs during brazing work for stainless steel heat exchangers used in refrigerant evaporators, condensers, hot water supply, etc. For this reason, nickel brazing filler metals with good corrosion resistance and a melting temperature that allows the brazing temperature to be reduced are required, and the development of a low-melting-point nickel brazing filler metal that satisfies these characteristics has become a challenge. An object of the present invention is to solve the above-mentioned problems in the conventional technology and to provide a nickel brazing material that has excellent corrosion resistance and exhibits sufficiently large wet spreadability even at a brazing temperature lower than that of conventional products. [Means for solving the problem]
[0009] In the present invention, in order to develop an alloy composition for developing a nickel brazing material having a melting temperature and wettability that enable a reduction in the brazing temperature, and also having excellent corrosion resistance, the following targets were set and all of them had to be satisfied as conditions. (Target value) (1) Melting temperature [liquidus temperature] → 1000℃ or less (2) Wetting and spreading properties [wax spreading coefficient] → 10 or more (3) Corrosion resistance [Weight loss due to corrosion in sulfuric acid] → 0.50 mg / m 2 ·s or less
[0010] The alloy (nickel brazing filler metal) of the present invention, which satisfies all of the above target values, has a melting temperature of 1000°C or less and is corrosion resistant to acids, and is characterized by its composition containing 8.0 to 19.0 mass% Cr, 7.0 to 10.5 mass% P, 0.1 to 1.5 mass% B, 2.0 to 8.0 mass% Cu, a Mo content of 10.0 mass% or less, a Si content of 2.5 mass% or less, and the balance being Ni and unavoidable impurities. Here, the inevitable impurities refer to impurities that are not intentionally added but are inevitably mixed in during the manufacturing process of each raw material, etc. Examples of such impurities include Al, C, Ti, Mg, S, O, N, V, Zr, Sn, etc., and the total amount of these is usually 0.3 mass% or less, which is not enough to affect the action of the present invention.
[0011] Furthermore, the nickel brazing material of the present invention is a nickel brazing material having the above-mentioned characteristics, further characterized in that it contains one or more elements selected from the group consisting of Co, Fe and Mn as elements that do not adversely affect the characteristics, and that the Co content is 5.0 mass% or less, the Fe content is 3.0 mass% or less, the Mn content is 3.0 mass% or less, and the total content of Co, Fe and Mn is 8.0 mass% or less.
[0012] The reasons for limiting the ranges of each component in the present invention as described above will be explained below.
[0013] Cr dissolves in Ni solid solution to improve the corrosion resistance of the alloy, but if the content is less than 8.0 mass%, sufficient effect cannot be obtained. On the other hand, if the content exceeds 19.0 mass%, the melting temperature increases and the wettability to the base material decreases during the brazing process, resulting in a decrease in brazing workability. For this reason, the Cr content is set to the range of 8.0 to 19.0 mass%.
[0014] P has the effect of lowering the melting temperature of the alloy through a eutectic reaction with Ni, and also improves the fluidity and wettability to the stainless steel substrate, but if it is less than 7.0 mass%, the effect is not fully exhibited. Also, if it exceeds 10.5 mass%, a hypereutectic composition is formed, which increases the melting temperature and reduces the wettability. Therefore, the P content is set to the range of 7.0 to 10.5 mass%.
[0015] Like P, B has the effect of lowering the melting temperature of the alloy through a eutectic reaction with Ni, and also acts as a flux to improve brazing workability, but if the content is less than 0.1 mass%, this effect is not fully exerted. Also, if the content exceeds 1.5 mass%, a compound with Cr is formed, causing a large increase in the melting temperature. Therefore, the B content is set to the range of 0.1 to 1.5 mass%.
[0016] Cu dissolves in Ni solid solution, contributing to a lowering of the melting temperature and improving the corrosion resistance. However, if the Cu content is less than 2.0 mass%, this effect is insufficient, and if the Cu content exceeds 8.0 mass%, the melting temperature increases. Therefore, the Cu content is set to the range of 2.0 to 8.0 mass%.
[0017] Mo dissolves in Ni solid solution, contributing to a decrease in melting temperature and also having the effect of improving corrosion resistance, and may be added as desired. If the Mo content exceeds 10.0 mass%, the melting temperature increases and the wet spreadability decreases, so the Mo content is set to a range of 10.0 mass% or less.
[0018] Like P and B, Si has the effect of lowering the melting temperature of the alloy by eutectic reaction with Ni, and also has the effect of improving brazing workability by exerting a flux action, so it may be added optionally, but if the Si content exceeds 2.5 mass%, a hypereutectic composition will be formed, which will increase the melting temperature and reduce the wettability. Therefore, the Si content is set to a range of 2.5 mass% or less.
[0019] In addition, the nickel brazing material of the present invention may contain 5.0 mass% or less Co, 3.0 mass% or less Fe, and 3.0 mass% or less Mn as elements that do not adversely affect the properties. These components may be blended alone or together, but the blending ratio of each component is limited to the above range because the wet spreadability decreases when Co, Fe, and Mn exceed the upper limit of the range. In addition, in the present invention, in order to satisfy the target corrosion resistance, material strength, and melting temperature setting values, the upper limit of the total of Co, Fe, and Mn is set to 8.0 mass%. In the present invention, the upper limit of the total is particularly preferably 4.0 mass% or less. The Ni content in the nickel brazing material of the present invention is 60 to 80 mass %. Effect of the Invention
[0020] The nickel brazing filler metal of the present invention has a liquidus temperature of 1000°C or less and has excellent wettability and spreadability, which makes it possible to reduce the brazing temperature (energy cost) and is effective when applied to stainless steel heat exchangers used for refrigerant evaporators, condensers, hot water supply, etc. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a schematic diagram for explaining a brazing test of a brazing alloy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The nickel brazing filler metal of the present invention can be obtained by completely melting an ingot containing base Ni and additive components Cr, P, B, Cu, Mo, and Si adjusted to a predetermined mass%, with predetermined amounts of Co, Fe, Mn, etc. added as necessary, in a crucible of a melting furnace, and then converting the molten alloy into powder by atomization or melt grinding, or by casting it into a predetermined mold to form a rod or plate.
[0023] In particular, with alloy powder produced by the atomization method, after adjusting the particle size to suit the intended application method, various methods can be freely selected to install the nickel brazing material of the present invention on the stainless steel base material, such as sprinkling (scattering) the binder and powder on the base material surface, mixing the binder and powder into a paste form and applying it, processing it into a sheet or foil form and installing it, or spraying the powder and installing it. EXAMPLES
[0024] The nickel brazing filler metals (example alloys) of the present invention adjusted and blended as described above and nickel brazing filler metals (comparison alloys) having compositions outside the composition range defined in claim 1 of the present application were melted and prepared, and the liquidus temperatures, brazing filler spread coefficients, and corrosion weight losses in sulfuric acid were measured and evaluated by the methods described below.
[0025] (1) Liquidus temperature measurement: 100g of ingots of each alloy composition were heated to about 1500℃ in an argon gas stream in an electric furnace to melt them, and then the melting temperature was measured by a thermal analysis method in which the temperature of the alloy was continuously measured while it was naturally cooled in the furnace. That is, a thermal analysis curve was drawn on a recorder connected to a thermocouple inserted in the center of the molten metal, and the liquidus temperature was read from the cooling curve.
[0026] (2) Measurement of brazing filler spreading coefficient: The alloy of the example was melted in an electric furnace in an argon gas atmosphere, and the molten metal was cast into a graphite mold to obtain a rod-shaped cast piece of 5 mmφ, which was then cut into pieces weighing about 0.5 g to obtain brazing filler metal samples. Next, as shown in Figure 1(a), the brazing filler metal sample was placed on a SUS304 stainless steel base material and heated at 980°C for 30 minutes and 10 -2 ~10 -1 The brazing heat treatment (hereinafter referred to as brazing) was carried out in a vacuum of 100 Pa. After brazing, the area S of the melted and spread brazing material was measured as shown in Figure 1(b), and the area S was divided by the cross-sectional area So of the sample before brazing to determine the brazing material spread coefficient W (=S / So), which was used as an index of the wettability of the brazing material alloy to the SUS304 stainless steel base material.
[0027] (3) Measurement of corrosion weight loss in sulfuric acid: The metal was melted in the same manner as in (1) above, and the molten metal was cast into a shell mold. The cast piece was then machined to approximately 10 x 10 x 20 mm to prepare a test piece. Next, a 1% aqueous sulfuric acid solution was prepared in a 300 cc beaker, and the test piece was placed in it to carry out a corrosion test using the full immersion method. The test conditions were a test temperature of 80°C and a test time of 6 hours. The amount of mass loss per unit area and unit time before and after the test was calculated to obtain the corrosion weight loss (mg / m 2 s) and the corrosion resistance to sulfuric acid was evaluated. The evaluation indicators are as follows: Corrosion weight loss ≦ 0.50mg / m 2 ·s:○" Corrosion weight loss > 0.50mg / m 2 ·s:×」
[0028] Table 1 shows examples of the present invention, and Tables 2 and 3 show comparative examples.
[0029] [Table 1]
[0030] [Table 2]
[0031] [Table 3]
[0032] Alloys No. 1 to No. 18 shown in Table 1 are examples of the present invention, and all of them have liquidus temperatures of 1000° C. or less. In addition, all of them have a brazing spread coefficient of 10 or more, which shows that the example alloys of the present invention have excellent wettability during brazing.
[0033] Furthermore, for sulfuric acid corrosion resistance, the corrosion weight loss under the test conditions was 0.50 mg / m 2 ·s or less, and it is understood that the example alloys of the present invention have good corrosion resistance to sulfuric acid.
[0034] On the other hand, in the alloys shown in Table 2, (a) to (n) are brazing filler metals with compositions outside the range of the alloys of the present invention, and at least one of the liquidus temperature, brazing filler spread coefficient, and sulfuric acid resistance properties does not meet the target value. Specifically, (a) and (b) are alloys with Cr contents outside the claimed range, (c) and (d) are alloys with P contents outside the claimed range, (e) and (f) are alloys with B contents outside the claimed range, (g) and (h) are alloys with Cu contents outside the claimed range, (i) is alloys with Mo contents above the upper limit of the claimed range, and (j) is alloys with Si contents above the upper limit of the claimed range, and none of these alloys meets at least one of the target properties. (k), (l), and (m) are alloys with Co, Fe, and Mn contents above the upper limit of the claimed range, and (n) is alloys with the total value of Co, Fe, and Mn above the upper limit of the claimed range, and none of these alloys meets at least one of the target properties.
[0035] Comparative brazing filler metals (A), (B), and (C) shown in Table 3 have nickel brazing filler metal compositions stipulated in the conventional JIS and AWS standards. Comparative brazing filler metals (D) to (J) are nickel brazing filler metals of prior art documents described in Japanese Patent No. 3168158, Japanese Patent Publication No. 2007-75867, Japanese Patent Publication No. 2009-202198, Japanese Patent Publication No. 2011-110575, Japanese Patent Publication No. 2012-55914, WO2015 / 156066, and Japanese Patent Publication No. 2017-131968. None of the brazing filler metals shown in Table 3 meets at least one of the target values for liquidus temperature, braze spread coefficient, and sulfuric acid corrosion resistance.
[0036] The nickel brazing filler metal of the present invention (example alloy) exhibits good wettability to various stainless steel base materials, and exhibits good brazing properties not only in a vacuum but also in a reducing hydrogen atmosphere or an inert argon atmosphere. [Industrial Applicability]
[0037] As described above in detail, the nickel brazing filler metal of the present invention has a melting temperature of 1000°C or less, has excellent wettability during brazing, and exhibits good corrosion resistance against acids such as sulfuric acid. Therefore, it is suitable for joining (brazing) to various stainless steel components and can be widely used not only in refrigerant evaporators, condensers, and hot water supply applications, but also in heat exchangers related to the environment and energy. [Explanation of symbols]
[0038] So: Cross-sectional area of brazing material sample S: Spread area of alloy after brazing W: Brazing spread coefficient (S / So) 1: Base material (SUS304 stainless steel) 2: Brazing material sample before brazing (φ5mm, approx. 0.5g) 3: Melted and spread brazing alloy after brazing
Claims
1. A nickel brazing filler metal having a melting temperature of 1000°C or less, excellent wet spreadability, and corrosion resistance to acid, the nickel brazing filler metal comprising 8.0 to 19.0 mass% Cr, 7.0 to 10.5 mass% P, 0.1 to 1.5 mass% B, 2.0 to 8.0 mass% Cu, an Mo content of 10.0 mass% or less, an Si content of 2.5 mass% or less, and the balance consisting of Ni and unavoidable impurities.
2. The nickel brazing material according to claim 1, further comprising one or more elements selected from the group consisting of Co, Fe, and Mn as elements that do not adversely affect the characteristics, the Co content being 5.0 mass% or less, the Fe content being 3.0 mass% or less, the Mn content being 3.0 mass% or less, and the total content of Co, Fe, and Mn being 8.0 mass% or less.
Citation Information
Patent Citations
Nickel-based brazing material and method for preparing alloy coating by nickel-based brazing material
CN102941418A
Ni BRAZING FILLER METAL ALLOY
JP2007075867A
Ni-Cu-BASED BRAZING FILLER METAL FOR HEAT EXCHANGER
JP2009202198A
Nickel-base alloy for brazing and brazing method
JP2009545451A
Ni-Fe-BASED ALLOY BRAZING MATERIAL
JP2011110575A